Tekanan Darah Terkontrol dengan Rutin Pemeriksaan pada Program International Partnership Real Work College di Kampung Pandan Malaysia: Controlled Blood Pressure with Routine Examinations at the International Partnership Real Work College Program in Kampung Pandan Malaysia - Firdaus, Okka Hafiizh; Fatmawati, Ariani; Syabariyah, Sitti; Yualita, Perla; Yuliani, Anita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Hypertension or high blood pressure is a severe global health problem and is often a significant risk factor for cardiovascular disease. Monitoring blood pressure regularly can help identify potential health problems quickly, enabling better treatment and preventive measures to avoid more severe problems, especially in cases of hypertension. Community service was conducted on Sunday, July 30, 2023, using a direct examination approach to residents who attended the PRIM & PRIA Kampung Pandan Malaysia branch deliberation event. The results of the examination showed that 20 residents were suffering from hypertension, or 46% of participants were suffering from hypertension. Twenty-three residents do not suffer from hypertension, 54%. Hypertension is characterized by increased blood pressure in the body's arteries, which can cause severe complications if not treated properly. Adults should check their blood pressure regularly as part of preventive health care. We encourage people to check their blood pressure regularly, especially if they are at high risk or have a family history of high blood pressure. Routine examinations allow for early detection and good management.